Routine cervical screening by primary HPV testing: early findings in the renewed National Cervical Screening Program. Issue 3 (5th June 2019) - Machalek, Dorothy A; Roberts, Jennifer M; Garland, Suzanne M; Thurloe, Julia; Richards, Adele; Chambers, Ian; Sivertsen, Terri; Farnsworth, Annabelle
Abstract: Objectives: To report human papillomavirus (HPV) testing patterns and rates of oncogenic HPV‐positivity for specimens submitted during the first 6 months after the National Cervical Screening Program switched from cytology‐ to primary HPV‐based screening. Design, participants: Retrospective cross‐sectional review of 195 606 specimens submitted for HPV testing, 1 December 2017 – 31 May 2018. Setting: Large community‐based general pathology laboratory in metropolitan Sydney. Main outcome measures: Prevalence of oncogenic HPV types (all, HPV16/18, non‐HPV16/18) by reason for HPV test (primary screening, non‐screening); for oncogenic HPV‐positive women in the age band recommended for primary HPV screening (25–74 years), prevalence of cytologic abnormality and rates of 12‐month follow‐up and colposcopy recommendations. Results: 195 606 samples were received: 157 700 (80.6%) for primary screening, 37 906 (19.4%) for non‐screening tests. Oncogenic HPV was detected in 8.1% of screening tests (95% CI, 7.9–8.2%) and 20.9% of non‐screening tests (95% CI, 20.5–21.3%); 35.5% (95% CI, 34.7–36.4%) of women of recommended screening age with positive oncogenic HPV screening test results also had a cytologic abnormality. The proportion of HPV16/18‐positive samples with high grade abnormality was 15.3% (95% CI, 14.2–16.6%); for samples positive for other oncogenic HPV types, the proportion was 6.3% (95% CI, 5.8–6.8%). Repeat HPV testing after 12 months was recommended for 5.4% (95% CI, 5.3–5.5%) and direct colposcopy for 2.6% (95% CI, 2.5–2.7%) of screened women aged 25–74 years. Conclusions: High grade cytologic abnormalities were more common in women positive for HPV16/18, supporting their higher risk classification. Colposcopy referral rates were higher than during primary cytology‐based testing, as predicted by clinical trial and modelling data. The prevalence of HPV was much higher in non‐screening than in primary screening samples. Our findings indicate the renewed program is performing as expected during the initial HPV screening round.